Glomerular filtration rate decline as a surrogate end point in kidney disease progression trials - Badve, Sunil V.; Palmer, Suetonia C.; Hawley, Carmel M.; Pascoe, Elaine M.; Strippoli, Giovanni F.M.; Johnson, David W. (Nephrology, dialysis, transplantation, 2016)
Chronic kidney disease (CKD) is strongly associated with increased risks of progression to end-stage kidney disease (ESKD) and mortality. Clinical trials evaluating CKD progression commonly use a composite end point of death, ESKD or serum creatinine doubling. However, due to low event rates, such trials require large sample sizes and long-term follow-up for adequate statistical power. As a result, very few interventions targeting CKD progression have been tested in randomized controlled trials. To overcome this problem, the National Kidney Foundation and Food and Drug Administration conducted a series of analyses to determine whether an end point of 30 or 40% decline in estimated glomerular filtration rate (eGFR) over 2-3 years can substitute for serum creatinine doubling in the composite end point. These analyses demonstrated that these alternate kidney end points were significantly associated with subsequent risks of ESKD and death. However, the association between, and consistency of treatment effects on eGFR decline and clinical end points were influenced by baseline eGFR, follow-up duration and acute hemodynamic effects. The investigators concluded that a 40% eGFR decline is broadly acceptable as a kidney end point across a wide baseline eGFR range and that a 30% eGFR decline may be acceptable in some situations. Although these alternate kidney end points could potentially allow investigators to conduct shorter duration clinical trials with smaller sample sizes thereby generating evidence to guide clinical decision-making in a timely manner, it is uncertain whether these end points will improve trial efficiency and feasibility. This review critically appraises the evidence, strengths and limitations pertaining to eGFR end points.